Pediatric tracheostomy, its indications, outcome and need for family education: a study in a tertiary hospital - Sharma, Kalpana; Basumatary, Phoebe Sarah (International Journal of Research in Medical Sciences, 2024)
Background: Paediatric age group remains a challenging patient group for any kind of surgical intervention. Tracheostomy in this age group remains a challenge and its indications have evolved and shifted over the years. Methods: A prospective study of 1 year period where patients below 18 years of age undergoing tracheostomy were studied and analyzed. Literature for existing protocols/guidelines were studied and implemented. Data was grouped according to age, gender, indications, contraindications, decannulation trends, complications and mortality outcome. Results: 17 elective paediatric tracheostomies were done out of which 5 patients were female and 12 were male. In the <1 year age group there were 2 patients (12%), 4 (24%) in the 1-5 years group, 5 (29%) in 6-10 years and 6 (35%) in the 11-18 years age bracket. Commonest indication was prolonged intubation (41.18%) followed by upper airway obstruction (29.41%). Complications that we faced which was the most common was blockage of tube (46.67%), followed by decannulation difficulty (20%). Conclusions: It is still a major challenge to standardize protocols for tracheostomy in paediatric age group as well as initiation of the care giver at home to follow adequate measures to manage children needing prolonged tracheostomy tube care.